Long-sized film, and method for producing the same
By controlling the cooling conditions and surface roughness of tetrafluoroethylene polymer films, the challenges of producing wide, thick films with excellent optical, heat resistance, and electrical properties are addressed, resulting in films suitable for electronic device applications.
Patent Information
- Application Number
- JP2023147784
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
The development of wide and thick tetrafluoroethylene polymer films with excellent optical, heat resistance, and electrical properties is challenging, particularly for applications in electronic devices where films with specific surface roughness and optical properties are required.
A long film containing a tetrafluoroethylene polymer is produced by controlling the cooling conditions of an aqueous dispersion with specific particle size range tetrafluoroethylene polymer particles, or by coating it on a substrate and baking it, ensuring the maximum surface height (Sz) is within a specified range for optimal optical properties.
The resulting film exhibits excellent heat resistance, electrical properties, and optical properties, including high total light transmittance and low haze, making it suitable for various electronic device applications.
Smart Images

Figure 2025040770000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a long film containing a tetrafluoroethylene-based polymer and a method for producing the same. [Background technology]
[0002] In recent years, in order to keep up with the increasing speed and frequency of mobile communication devices such as mobile phones, materials with high thermal conductivity, low linear expansion coefficient, low dielectric constant and low dielectric loss tangent are required for printed circuit boards of communication devices. In response to such requirements, for example, base films composed of polyimide (PI), liquid crystal polymer (LCP) with low dielectric properties, polyphenylene sulfide (PPS), etc. have been proposed for flexible printed circuit board (FPC) applications. Patent Document 1 proposes a printed wiring board having a polyimide base film that is insulating and has a specific surface property, and a conductive layer on at least one surface of the polyimide base film. On the other hand, tetrafluoroethylene polymers have been attracting attention as materials that have high thermal conductivity, low linear expansion coefficient, low dielectric constant, low dielectric loss tangent, and excellent transparency compared to materials such as PI, LCP, and PPS. In particular, films with small surface roughness have low haze and excellent dimensional stability, and tend to be preferred as the substrate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 104420 Summary of the Invention [Problem to be solved by the invention]
[0004] As transmission signals become faster and at higher frequencies, there has been active development of electromagnetic wave reflectors (reflector arrays), also known as metasurface reflectors, metasurface substrates, solar cell module parts such as release plates on the surface of solar cells, transparent cover films, etc., for various electronic devices such as smartphones and tablet computers. When applying tetrafluoroethylene-based polymers to the above-mentioned fields of use, a film that is wide in width and has a certain degree of thickness and also has excellent optical properties is required. The present inventors, in investigating how to improve the optical properties of a long film of a tetrafluoroethylene-based polymer by making it wider and thicker, have found that controlling the maximum height (Sz) at a specified position on the surface within a specified range results in a long film with excellent optical properties. The inventors also found that such a long film can be preferably produced by extruding or applying an aqueous dispersion having a predetermined concentration of tetrafluoroethylene-based polymer particles in a specific particle size range onto a substrate layer, and controlling the cooling conditions during baking to form the film, thereby completing the present invention. An object of the present invention is to provide a long film containing a wide and thick tetrafluoroethylene-based polymer, which has excellent heat resistance and electrical properties as well as excellent optical properties, and a method for producing the same. [Means for solving the problem]
[0005] The present invention has the following aspects. [1] A long film containing a tetrafluoroethylene-based polymer, wherein when the short direction (TD) of the long film is divided at 200 mm intervals, the endmost divided parts are the TD direction end parts and the central divided part is the TD direction central part, and the maximum height Sz value of the TD direction end parts (end Sz value) and the maximum height Sz value of the TD direction central part (central Sz value) specified in ISO25178 are each 0.5 μm or more, and the ratio of the end Sz value to the central Sz value is in the range of 1±0.5, and the total light transmittance of the film specified in JIS R 3106 is 90% or more and the haze is less than 1.5%, and the long film has a thickness of 10 μm or more and a width of 1,000 mm or more. [2] The long film according to [1], wherein the tetrafluoroethylene-based polymer is a heat-fusible tetrafluoroethylene-based polymer having a melting point of 260 to 320°C. [3] The heat-fusible tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and the carbonyl group-containing group is 1×10 carbon atoms constituting the polymer main chain. 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol% or more but less than 97.5 mol% and more than 2.5 mol% but not more than 10 mol% of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 A long film of [1] or [2], which is a polymer having less than 100 particles per unit area. [4] A method for producing a long film according to any one of [1] to [3], comprising extruding a dispersion containing 100 parts by mass of tetrafluoroethylene-based polymer particles having an average particle size of 1 μm or more and less than 10 μm and 80 to 300 parts by mass of water, the dispersion containing particles having a particle size of 20 to 80 μm at a concentration of 5 to 100 particles / ml as measured by a particle counter, forming a film containing the tetrafluoroethylene-based polymer, heating the film to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer, and cooling at a rate of 50 to 100° C. / min, or coating a substrate with the dispersion to form a coating layer made of the dispersion on the surface of the substrate, heating the substrate having the coating layer to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer on the surface of the substrate, and cooling at a rate of 50 to 100° C. / min. [5] The method according to [4], wherein the tetrafluoroethylene polymer is a heat-fusible tetrafluoroethylene polymer having a melting point of 260 to 320°C. [6] The heat-fusible tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and the carbonyl group-containing group is 1×10 carbon atoms constituting the polymer main chain. 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol% or more but less than 97.5 mol% and more than 2.5 mol% but not more than 10 mol% of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 The method according to [4] or [5], wherein the polymer has less than 100 molecular weight units per unit area. [7] The method according to any one of [4] to [6], wherein the content of the tetrafluoroethylene polymer particles is 30% by mass or more. [8] The method according to any one of [4] to [7], wherein the dispersion further contains 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m. Effect of the Invention
[0006] According to the present invention, it is possible to provide a wide, thick, long film containing a tetrafluoroethylene-based polymer, which has excellent heat resistance and electrical properties as well as excellent optical properties, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The following terms have the following meanings: The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit." "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). The "glass transition temperature (Tg)" is a value measured by analyzing a polymer using the dynamic mechanical analysis (DMA) method. "Average particle size (D50)" is the volume-based cumulative 50% diameter of particles determined by laser diffraction / scattering. In other words, particle size distribution is measured by laser diffraction / scattering, and a cumulative curve is calculated with the total volume of the particle group as 100%, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of particles is determined by dispersing the particles in water and analyzing them by the laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). "Average particle size (D90)" is the volume-based cumulative 90% diameter of the particles, calculated in the same manner as for D50. The specific surface area of a particle is a value calculated by measuring the particle by a gas adsorption (constant volume method) BET multipoint method, and is determined using a NOVA4200e (manufactured by Quantachrome Instruments). The "viscosity" is determined by measuring the composition using a Brookfield viscometer at 25° C. and 30 rpm. The measurement is repeated three times, and the average value of the three measured values is calculated. The "thixotropy ratio" is a value calculated by dividing the viscosity η1 of the composition measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values is used. The "surface tension" of a solvent or solution is a value measured by the Wilhelmy method at 25°C using a surface tensiometer.
[0008] The present invention is a long film containing a tetrafluoroethylene-based polymer (hereinafter also referred to as "F polymer"), in which when the short direction (TD direction) of the long film is divided at 200 mm intervals, the endmost divided parts are the TD direction end parts and the central divided part is the TD direction central part, the maximum height Sz value of the TD direction end parts (end Sz value) and the maximum height Sz value of the TD direction central part (central Sz value) specified in ISO25178 are each 0.5 μm or more, and the ratio of the end Sz value to the central Sz value is in the range of 1±0.5, and the total light transmittance of the film specified in JIS R 3106 is 90% or more and the haze is less than 1.5% (hereinafter also referred to as "the film").
[0009] This film has excellent physical properties based on the F polymer, such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric tangent), as well as excellent optical properties such as total light transmittance and haze. In this film, when the film is divided at intervals of 200 mm in the short direction (TD direction), the endmost divided part is the TD direction end part, and the central divided part is the TD direction central part, and the relationship between the maximum height Sz value of the TD direction end part (end Sz value) and the maximum height Sz value of the TD direction central part (central Sz value) as specified in ISO25178 respectively meets a predetermined range. In other words, when the surface roughness of this film is considered from the viewpoint of the maximum height Sz value, the Sz value is converged to a predetermined range in the TD direction of this film. This contributes to the improvement of the optical properties of this film, and it is considered that the total light transmittance and haze specified in the present invention have been achieved. The control of the end Sz value and the central Sz value in the present film can be suitably performed by the manufacturing method described later. In particular, when the molten F polymer is solidified by cooling, if the cooling is rapid, cracks and breaks are likely to occur, and the variation in the maximum height Sz value is likely to increase. On the other hand, if the cooling is slow, the F polymer is likely to concentrate in the part where solidification begins, and the variation in the maximum height Sz value is also likely to increase. In particular, in the case of a long film having a thickness of 10 μm or more and a width of 1000 mm or more such as the present film, the molten F polymer is likely to cool at the end of the film in the TD direction, while it tends to be difficult to cool in the central part in the TD direction because the F polymer is continuously present on both sides of the film, and therefore the variation in cooling is likely to increase. By controlling the degree of cooling, the present film in which the maximum height Sz value converges to a predetermined range in the TD direction can be suitably manufactured. Furthermore, by controlling the surface roughness of the present film, the adhesion to various substrates such as metal foils can be improved.
[0010] In this film, when the film is divided at 200 mm intervals in the short direction (TD direction), with the endmost divided parts being the TD direction end parts and the central divided part being the TD direction central part, the maximum height Sz value of the TD direction end parts (end Sz value) and the maximum height Sz value of the TD direction central part (central Sz value), as specified in ISO25178, are each 0.5 μm or more, and the ratio of the end Sz value to the central Sz value is in the range of 1±0.5. Both the end Sz value and the center Sz value are preferably 0.9 μm or more, more preferably 1.0 μm or more. On the other hand, both the end Sz value and the center Sz value are preferably less than 8 μm, more preferably less than 5 μm. Also, the ratio of the end Sz value to the center Sz value is preferably in the range of 1±0.40, more preferably in the range of 1±0.25. When the maximum height Sz value of the surface of the present film as defined by ISO25178 is within the above range, the above-mentioned action and effect are more effectively achieved, and the optical properties of the present film are more excellent. Also, the adhesion between the present film and the base layer can be maintained. The maximum height Sz can be measured, for example, by a laser microscope.
[0011] The total light transmittance of the film is 90% or more and the haze is less than 1.5%, as specified by JIS R 3106. The total light transmittance of the film is preferably 95% or more. On the other hand, the haze of the film is preferably 1.2% or less, and more preferably 1% or less. By controlling the end Sz value and central Sz value of the present film within the above ranges, these excellent optical properties can be achieved. The thickness of the present film is 10 μm or more, preferably 25 μm or more, and more preferably 50 μm or more, while the thickness of the present film is preferably 1000 μm or less, and more preferably 500 μm or less. The width of the film is 1000 mm or more, preferably 1200 mm or more, while the width of the film is preferably 5000 mm or less, more preferably 2000 mm or less.
[0012] The F polymer in the present invention is a polymer containing units based on tetrafluoroethylene (hereinafter also referred to as "TFE") (hereinafter also referred to as "TFE units"). The F polymer is preferably heat-fusible. Here, a heat-fusible polymer means a polymer that has a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The melting temperature of the F polymer is preferably 200° C. or higher, more preferably 260° C. or higher. The melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower. The melting temperature of the F polymer is preferably 200 to 320° C. In this case, the present film tends to have excellent heat resistance.
[0013] The glass transition point of the F polymer is preferably 50° C. or higher, more preferably 75° C. or higher. The glass transition point of the F polymer is preferably 150° C. or lower, more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a mixture for wetting tension testing (manufactured by Wako Pure Chemical Industries, Ltd.) specified in JIS K 6768 on a flat plate made of the F polymer.
[0014] F polymer is preferably a polymer containing TFE unit and ethylene-based unit (ETFE), a polymer containing TFE unit and propylene-based unit, a polymer containing TFE unit and perfluoro(alkyl vinyl ether) (PAVE)-based unit (PAVE unit) (PFA), a polymer containing TFE unit and hexafluoropropylene-based unit (FEP), more preferably PFA and FEP, and even more preferably PFA. These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.
[0015] The F polymer preferably has an oxygen-containing polar group, more preferably has a hydroxyl- or carbonyl-containing group, and even more preferably has a carbonyl-containing group. In this case, the film tends to have excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric tangent). The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), a formyl group, a halogenoformyl group, a urethane group (-NHC(O)O-), a carbamoyl group (-C(O)-NH2), a ureido group (-NH-C(O)-NH2), an oxamoyl group (-NH-C(O)-C(O)-NH2) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue. When the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6 The number of oxygen-containing polar groups per unit is preferably 10 to 5000, more preferably 100 to 3000. The number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.
[0016] The oxygen-containing polar group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment.
[0017] The F polymer contains TFE units and PAVE units in the order of more than 97.5 mol% and less than 99.5 mol%, and 0.5 mol% or more and less than 2.5 mol%, and has a carbonyl group-containing group in an amount of 1×10 6 or a polymer (1) containing TFE units and PAVE units in the order of 90 mol % or more and less than 97.5 mol %, more than 2.5 mol % and 10 mol % or less, and the number of carbonyl group-containing groups is 1×10 6 Polymers (2) having less than 100 per unit area are preferred. If such an F polymer is used, spherulites having a relatively small radius are easily formed, so that the surface properties of the present film are easily improved and the maximum height Sz value is easily controlled to the above-mentioned specified range as specified by ISO25178.
[0018] The polymer (1) is more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in the order of more than 97.5 mol% and less than 99.5 mol%, 0.5 mol% or more and less than 2.2 mol%, and 0.01 to 0.3 mol% relative to the total units. Specific examples of such F polymers include the polymers described in WO 2018 / 16644. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.
[0019] The polymer (2) is more preferably composed of only TFE units and PAVE units, and contains more than 2.5 mol % and not more than 5.0 mol % of PAVE units based on all units. The number of carbonyl-containing groups in polymer (2) is 1×10 6 More preferably, the number per carbonyl group is less than 50. The lower limit of the number of the carbonyl group-containing groups is 1. The polymer (2) may be produced by using a polymerization initiator or a chain transfer agent that does not generate a carbonyl group-containing group as a terminal group of the polymer chain, or by fluorinating an F polymer having a carbonyl group-containing group (such as an F polymer having an oxygen-containing polar group derived from a polymerization initiator at the terminal group of the polymer main chain). Examples of the fluorination method include a method using fluorine gas (see JP 2019-194314 A, etc.).
[0020] The present film can be suitably produced, for example, by extruding a dispersion (hereinafter also referred to as the present dispersion) containing 100 parts by mass of F polymer particles (hereinafter also referred to as "F particles") having an average particle size of 1 μm or more and less than 10 μm, and 80 to 300 parts by mass of water, and having a particle concentration of 5 to 100 particles / ml having a particle size of 20 to 80 μm measured with a particle counter, to form a film containing the F polymer, heating the film to form a resin layer containing a molten sintered body of the F polymer, and cooling at 50 to 100 ° C. / min, or by applying the present dispersion to a substrate to form a coating layer made of the present dispersion on the substrate surface, heating the substrate having the coating layer to form a resin layer containing a molten sintered body of the F polymer on the substrate surface, and cooling at 50 to 100 ° C. / min. That is, the present invention also relates to a method for producing a long film (hereinafter also referred to as "this method"), which comprises extruding the present dispersion to form a film containing the F polymer, heating the film to form a resin layer containing a molten sintered body of the F polymer, and cooling at 50 to 100°C / min, or coating a substrate with the present dispersion to form a coating layer made of the present dispersion on the surface of the substrate, heating the substrate having the coating layer to form a resin layer containing a molten sintered body of the F polymer on the surface of the substrate, and cooling at 50 to 100°C / min.
[0021] In this method, the F particles contained in the dispersion are particles that include an F polymer, and preferably consist of an F polymer. The D50 of the F particles is 1 μm or more and less than 10 μm. The F particles may be solid particles or non-hollow particles. The F particles may be secondary particles formed from nanometer-order fine particles. The D50 of the F particles is preferably 1.0 μm or more, more preferably 1.5 μm or more. The D50 of the F particles is preferably 6 μm or less, more preferably 5 μm or less. Furthermore, D90 of the F particles is preferably 8 μm or less, and more preferably 6 μm or less. When the D50 and D90 of the F particles are within the above ranges, the dispersion liquid is likely to have excellent dispersion stability and handleability, and the dispersion liquid is likely to have a particle concentration of 5 to 100 particles / ml having a particle diameter of 20 to 80 μm as measured with a particle counter. One type of F particle may be used, or two or more types of F particles may be used.
[0022] The specific surface area of F particles is 1 to 25 m 2 / g, and 6 to 15m 2 When the specific surface area of the F particles is within the above range, it is considered that the surfaces of the F particles are easily wetted and aggregates of the F particles are easily disintegrated, making it easier to obtain a dispersion liquid in which the concentration of particles having particle diameters of 20 to 80 μm measured with a particle counter is 5 to 100 particles / ml. In addition, the film formed from the dispersion liquid is more likely to satisfy the specified range of the maximum height Sz value described above, and is more likely to have excellent optical properties in addition to the physical properties inherent to the F polymer, such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant, and low dielectric tangent).
[0023] This dispersion contains 100 parts by mass of F particles and 80 to 300 parts by mass of water, and has a particle concentration of 5 to 100 particles / ml having a particle diameter of 20 to 80 μm as measured with a particle counter. The content of F particles in the present dispersion is preferably 25% by mass or more, more preferably 30% by mass or more, and is preferably 55% by mass or less, more preferably 50% by mass or less. The water content in the present dispersion is preferably 25% by mass or more, and more preferably 40% by mass or more. The water content is preferably less than 70% by mass, and more preferably 65% by mass or less. The water content in the present dispersion is preferably 60 to 180% by mass relative to the F particle content. In the present dispersion, the particle concentration of particles having a particle diameter of 20 to 80 μm measured by a particle counter is preferably 10 particles / ml or more. The particle concentration is preferably 80 particles / ml or less, more preferably 60 particles / ml or less. If the particle concentration is within the above range, in other words, if the content of coarse particles is small, the above-mentioned maximum height Sz value of the present film obtained by the present method can be easily controlled within a specific range.
[0024] The dispersion may further contain 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m. The water-soluble solvent having a surface tension of 20 to 30 mN / m is a compound that is liquid at 25°C under atmospheric pressure, preferably a compound having a boiling point of 160°C or less, more preferably a compound having a boiling point of 120°C or less. Such a water-soluble solvent is preferably azeotropic with water. In this specification, the water-soluble solvent means a solvent having a solubility in water of 100 g / L or more. The water-soluble solvent is preferably a monool having 1 to 6 carbon atoms, more preferably methanol (23 mN / m), ethanol (23 mN / m), 1-propanol (24 mN / m), 2-propanol (22 mN / m), 1-butanol (25 mN / m), 2-butanol (24 mN / m), isobutanol (23 mN / m), 1-methoxy-2-propanol (26 mN / m), 2-propoxy-ethanol (27 mN / m), 1-propoxy-2-propanol (25 mN / m), 2-ethoxyethanol (26 mN / m), and even more preferably ethanol. The numerical values in parentheses are the surface tensions of the monools. When the present dispersion further contains a water-soluble solvent, the amount is preferably 0.1 to 5 mass % or less based on the total amount of the present dispersion. The content of the water-soluble solvent in the present dispersion is preferably 1 to 10 mass % based on the content of the F particles. In the present dispersion, the water-soluble solvent is considered to play a role in adjusting the concentration of particles with a particle size of 20 to 80 μm, and also to play a role as an antifoaming agent such as a foam suppressing action or a foam breaking action.
[0025] The dispersion may further contain a nonionic surfactant, such as a glycol surfactant, an acetylene surfactant, a silicone surfactant, or a fluorine surfactant. Among these, nonionic surfactants having a hydroxyl group in the hydrophilic site are preferred, and organopolysiloxanes having a hydroxyl group or a polyoxyalkylene group are more preferred. When the present dispersion contains the above-mentioned nonionic surfactant, the above-mentioned mechanism of action is more easily manifested, and the dispersion stability and handleability of the F particles are more likely to be excellent. Furthermore, the rheological properties of the dispersion are improved, and handling properties such as film-forming properties tend to improve. The organopolysiloxane is more preferably a polyoxyalkylene-modified dimethylsiloxane having a polyoxyalkylene structure as the hydrophilic portion and a polydimethylsiloxane structure as the hydrophobic portion. Polyoxyalkylene-modified dimethylsiloxane has a polydimethylsiloxane unit (-(CH3)2SiO2 / 2 -), may have polydimethylsiloxane units in the side chain, or may have polydimethylsiloxane units in both the main chain and the side chain.
[0026] Specific examples of nonionic surfactants include the "Ftergent" series (manufactured by Neos), the "Surflon" series (manufactured by AGC Seimi Chemical Co., Ltd.), the "Megafac" series (manufactured by DIC Corporation), the "Unidyne" series (manufactured by Daikin Industries, Ltd.), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan), "KF-6011", "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.), and the "Tergitol" series (manufactured by The Dow Chemical Company, "Tergitol TMN-100X", etc.). The nonionic surfactant may be used alone or in combination of two or more kinds. When the present dispersion further contains a nonionic surfactant, the amount thereof is preferably within the range of 1 to 15 parts by mass relative to 100 parts by mass of the present dispersion.
[0027] The dispersion may further contain a water-soluble polymer, such as at least one selected from the group consisting of vinyl alcohol polymers, acrylic polymers, polyvinylpyrrolidone, polypyrrole, polythiophene, polyethyleneimine, and cellulose ether. In this specification, the term "water-soluble polymer" refers to a polymer having a solubility in water of 20 g / L or more. When the present dispersion contains the above-mentioned water-soluble polymer, the above-mentioned mechanism of action is more easily exhibited, and the concentration of particles having a particle size of 20 to 80 μm in the present dispersion can be easily adjusted to a predetermined range, and the rheological properties of the present dispersion are improved, and the handling properties such as film-forming properties are easily improved.
[0028] Examples of vinyl alcohol-based polymers include polyvinyl alcohol, polyvinyl acetate, partially acetylated or partially acetalized polyvinyl alcohol, and copolymers of vinyl alcohol, vinyl butyral, and vinyl acetate. Specific examples of vinyl alcohol-based polymers include the "S-LEC (registered trademark) B" series, the "S-LEC (registered trademark) K (KS)" series, and the "S-LEC (registered trademark) SV" series (all manufactured by Sekisui Chemical Co., Ltd.), and the "Mobital (registered trademark)" series (manufactured by Kuraray Co., Ltd.).
[0029] Specific examples of cellulose ethers include the "Sunrose (registered trademark)" series (manufactured by Nippon Paper Industries Co., Ltd.), the "Metolose (registered trademark)" series (manufactured by Shin-Etsu Chemical Co., Ltd.), and "HEC CF Grade" (manufactured by Sumitomo Seika Chemicals Co., Ltd.). The water-soluble polymer may be used alone or in combination with two or more kinds. When the present dispersion further contains a water-soluble polymer, the amount thereof is preferably within a range of 1 to 15 parts by mass relative to 100 parts by mass of the present dispersion.
[0030] In addition to water and the above-mentioned water-soluble solvent, the present dispersion may contain other dispersion media within the range that does not impair the effects of the present invention. Such other dispersion media are preferably miscible with the above-mentioned water-soluble solvent and water. Examples of other dispersion media include amides such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone; and ketones such as acetone and methyl ethyl ketone.
[0031] Here, the concentration of particles having a particle diameter of 20 to 80 μm as measured by a particle counter in this dispersion can be controlled to 5 to 100 particles / ml by, for example, using F particles having a specific specific surface area using a specific F polymer and dispersing them by controlling the blend ratio with water, and further including one or more of the above-mentioned water-soluble solvents, nonionic surfactants, and water-soluble polymers.
[0032] The present dispersion may further contain inorganic particles, in which case the F layer formed from the present dispersion is likely to have excellent electrical properties and low linear expansion. Examples of inorganic particles include silicon compounds such as quartz powder, silica, wollastonite, talc, silicon nitride, silicon carbide, and mica; nitrogen compounds such as boron nitride and aluminum nitride; metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide; carbon fibers; carbon allotropes such as graphite, graphene, and carbon nanotubes; and metals such as silver and copper. One type of inorganic particle may be used, or two or more types may be used in combination.
[0033] The present dispersion may further contain another resin different from the F polymer. Such another resin may be contained in the present dispersion as non-hollow particles, or may be dissolved or dispersed in a liquid dispersion medium (hereinafter also referred to as "liquid dispersion medium") such as water, a water-soluble solvent, or another dispersion medium that constitutes the present dispersion. As the other resin, aromatic polymers are preferable, for example, aromatic imide polymers can be mentioned.Specific examples of aromatic imide polymers include "UPIA-AT" series (UBE), "NEOPLIM (registered trademark)" series (Mitsubishi Gas Chemical Company, Inc.), "SPIXELIA (registered trademark)" series (Somar), "Q-PILON (registered trademark)" series (PI Technical Research Institute), "WINGO" series (Wingo Technology Co., Ltd.), "TOMAID (registered trademark)" series (T&K TOKA), "KPI-MX" series (Kawamura Sangyo Co., Ltd.), "HPC-1000" and "HPC-2100D" (both manufactured by Showa Denko Materials Co., Ltd.). When the present dispersion further contains another resin, the content of the other resin relative to the F particles is preferably 1 to 25% by weight.
[0034] The present dispersion may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, and a flame retardant.
[0035] The present dispersion is obtained by mixing 100 parts by mass of F particles, 80 to 300 parts by mass of water, and, if necessary, the water-soluble solvent, nonionic surfactant, other dispersion medium, inorganic particles, other resins, additives, etc. The present dispersion may be obtained by mixing F particles and water all at once, or by dividing and mixing them several times. In addition, there is no particular limitation on the order of mixing when the water-soluble solvent, nonionic surfactant, other dispersion medium, inorganic particles, other resins, additives, etc. are further mixed as necessary, and they may be mixed with the F particles in advance, may be added to water in advance and then mixed with the F particles, or may be mixed when the F particles and water are mixed.
[0036] Examples of mixing devices for obtaining the present dispersion include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.
[0037] The viscosity of the present dispersion is preferably 10 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the present dispersion is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less. In this case, the present dispersion has excellent coatability and is easy to form an F layer of any thickness. In addition, the present dispersion having a viscosity in this range is easy to highly express the physical properties of the F polymer in the F layer formed therefrom. The thixotropy ratio of the present dispersion is preferably 1.0 to 3.0, in which case the present dispersion has excellent coatability and homogeneity and is likely to produce a denser F layer. These liquid properties are likely to be improved when the present dispersion further contains the above-mentioned water-soluble polymer.
[0038] From the viewpoint of improving long-term storage stability, the pH of the present dispersion is more preferably 8 to 10. The pH of the present dispersion can be adjusted with a pH adjuster (amine, ammonia, citric acid, etc.) or a pH buffer (tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium hydrogen carbonate, ammonium carbonate, ammonium acetate, etc.).
[0039] In one embodiment of the method, the dispersion is extruded to form a film containing the F polymer. The extruded film may be further cast by press molding, calendar molding, etc. The film is heated to remove the liquid dispersion medium, forming a resin layer containing a molten sintered body of the F polymer, and cooled at 50 to 100°C / min. Such heating is preferably carried out in stages. Specifically, in the first heating, the film is heated near the glass transition temperature while maintaining the dispersed state of the F particles in the film, giving priority to minimizing changes in the state of the F particles themselves. Meanwhile, in the second heating, the film is heated to near the glass transition temperature while maintaining the dispersed state of the F particles in the film, giving priority to diffusing and removing liquid dispersion media such as water or water-soluble solvents from the coating layer, forming a layer containing F particles that is a dry coating with little distortion overall. Then, the dry coating is preferably baked to form a resin layer containing an F polymer. This stepwise drying allows the diffusion of the F particles to be balanced with the diffusion of the liquid dispersion medium while keeping the F particle aggregation largely eliminated, even when a dispersion liquid containing F particles, which generally have low affinity with other materials, is used, making it easier to converge the above-mentioned maximum height Sz value within the range specified in the present invention, and making it easier to form the present film having high adhesion, low transmission loss, and excellent optical properties. This tendency becomes more pronounced when the dispersion liquid further contains one or more of a water-soluble solvent, a nonionic surfactant, or a water-soluble polymer having a specific surface tension, because the surface of the F particles becomes more easily wetted, and the F particle aggregates are more easily broken down and uniformly dispersed.
[0040] As the stepwise heating, it is preferable to carry out the first heating in a temperature range of 25°C or higher, lower than the boiling point of water constituting the dispersion and lower than [the glass transition temperature of the F polymer + 10°C], followed by the second heating in a temperature range higher than the above temperature range and lower than the melting temperature of the F polymer. The lower limit of the initial heating temperature is preferably 40° C. or higher. The upper limit of the initial heating is preferably below the glass transition temperature of the F polymer. The second heating is preferably carried out in a temperature range that is at least 50° C. higher than the temperature range of the first heating and is at most [the melting temperature of the F polymer −100° C.]. Specifically, it is preferable that the temperature range of the first heating is 45 to 95°C, and the temperature range of the second heating is 100 to 150°C.
[0041] The above-mentioned first heating and second heating are both preferably performed for 1 to 30 minutes. In the first heating and second heating, the liquid dispersion medium does not need to be completely removed, and it is sufficient to remove it to the extent that the layer formed by the packing of the F particles can maintain a self-supporting film. In addition, in the first heating and second heating, air may be blown to promote removal of the liquid dispersion medium by air drying.
[0042] After the second heating, it is preferable to further heat the material in a temperature range equal to or higher than the melting temperature of the F polymer (hereinafter also referred to as "third heating") to obtain a resin layer containing a molten sintered body of the F polymer. Specifically, the temperature range of the third heating is preferably 340 to 400° C. The heating time of the third heating is preferably 0.1 to 30 minutes.
[0043] The heating device for each of the first heating, the second heating, and the third heating may be an oven or a ventilation drying furnace. The heat source in the device may be a contact type heat source (hot air, hot plate, etc.) or a non-contact type heat source (infrared rays, etc.). In this method, each heating step may be performed under normal pressure (atmospheric pressure) or reduced pressure, and the atmosphere in each heating step may be either air or inert gas (helium gas, neon gas, argon gas, nitrogen gas, etc.).
[0044] After forming the resin layer containing the molten sintered body of the F polymer, the film is obtained by cooling at 50 to 100°C / min. The cooling is preferably in the range of 60 to 90°C / min. The cooling is preferably performed so as to lower the temperature to at least the melting temperature of the F polymer. It is presumed that by controlling the cooling rate after baking the F polymer within the above-mentioned predetermined range, the rapid solidification of the molten F polymer is easily suppressed, the F polymer is prevented from being locally exposed or unevenly distributed on the surface, and the above-mentioned maximum height Sz value of the film is easily converged to the range specified in the present invention. The rate of temperature drop can be controlled by using a temperature control function associated with the above-mentioned oven or ventilated drying furnace as a heating device. Appropriate cooling such as air or water cooling may also be performed.
[0045] In another embodiment of the present method, the present dispersion is preferably applied to a long substrate to form a coating layer of the present dispersion on the surface of the substrate. Examples of the method for applying the present dispersion include a coating method, a droplet ejection method, and a dipping method, and the present method is preferably a roll coating method, a knife coating method, a bar coating method, a die coating method, or a spray method. Examples of the substrate include metal substrates such as metal foils of copper, nickel, aluminum, titanium, alloys thereof, etc.; heat-resistant resin films such as polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystalline polyester, and tetrafluoroethylene polymers; prepreg substrates (precursors of fiber-reinforced resin substrates); ceramic substrates (ceramic substrates such as silicon carbide, aluminum nitride, and silicon nitride); and glass substrates. The ten-point average roughness of the surface of the substrate is preferably 0.01 to 0.05 μm. The surface of the substrate may be surface-treated with a silane coupling agent or plasma-treated. As the silane coupling agent, a silane coupling agent having a functional group such as 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, or 3-isocyanatepropyltriethoxysilane is preferable. This method is favorable from the viewpoint of improving productivity because it allows the use of a roll-to-roll process and the film can be manufactured as a long product such as a roll.
[0046] Next, the substrate having the coating layer is heated to form a resin layer containing a molten sintered body of the F polymer on the surface of the substrate. Such heating is preferably performed stepwise, and the details are the same as those of the first heating, the second heating, and the third heating described above.
[0047] The present film is formed by extruding the present dispersion or applying it to a substrate, followed by a heating step, preferably the above-mentioned first heating, second heating, and third heating steps. These steps may be performed once each, or may be repeated two or more times. For example, the present dispersion may be applied to the surface of a substrate to obtain a coating layer, a resin layer may be formed by the first heating, second heating, and third heating, and the present dispersion may be applied to the surface of the resin layer to form a coating layer, and the present film may be formed by each of the above-mentioned heating steps. Alternatively, the present dispersion may be applied to the surface of a substrate to obtain a coating layer, and at the stage where the liquid dispersion medium is removed by the above-mentioned first heating and second heating, the present dispersion may be further applied to the surface, and the present film may be formed by each of the above-mentioned heating steps. The first heating may be carried out stepwise at a plurality of temperatures within the temperature range of the first heating, and the second heating may be carried out stepwise at a plurality of temperatures within the temperature range of the second heating.
[0048] After forming the resin layer containing the molten sintered body of the F polymer, the film is obtained by cooling at 50 to 100° C. / min. The details of the cooling are the same as those described above.
[0049] As described above, the present film is obtained by extruding the present dispersion to form a film containing an F polymer, heating the film to form a resin layer containing a molten sintered body of the F polymer, and cooling at 50 to 100 ° C. / min, or by applying the present dispersion to a substrate layer to first form a coating layer made of the present dispersion on the surface of the substrate layer, preferably through the first heating, second heating, and third heating steps to form a resin layer containing a molten sintered body of F particles, and cooling at 50 to 100 ° C. / min. In other words, it is only by going through such steps that the present film containing a molten sintered body of F particles that satisfies the above-mentioned predetermined range of Sz can be obtained.
[0050] The dielectric constant of the film is preferably 2.4 or less, more preferably 2.0 or less. The dielectric constant is preferably greater than 1.0. The dielectric tangent of the film is preferably 0.0022 or less, more preferably 0.0020 or less. The dielectric tangent is preferably greater than 0.0001. The thermal conductivity of the film is preferably 1 W / m·K or more, more preferably 3 W / m·K or more. The upper limit of the thermal conductivity of the film is 100 W / m·K. The thermal conductivity of the present film means the thermal conductivity in the in-plane direction of the present film.
[0051] The linear expansion coefficient of the present film is preferably 100 ppm / ° C. or less, and more preferably 80 ppm / ° C. or less. The lower limit of the linear expansion coefficient of the present film is 1 ppm / ° C. The linear expansion coefficient means a value obtained by measuring the linear expansion coefficient of a test piece in the range of 25° C. or more and 260° C. or less according to the measurement method specified in JIS C 6471:1995.
[0052] The present film may be further laminated with other layers, such as films of heat-resistant resins, such as liquid crystal polymers, such as polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystal polyester, and tetrafluoroethylene-based polymers other than F polymers, such as polytetrafluoroethylene; prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates, such as silicon carbide, aluminum nitride, and silicon nitride; glass substrates, and the like.
[0053] A laminate can be formed by laminating the present film on a substrate. Examples of a method for producing a laminate include a method of thermocompression bonding the present film and a substrate. In addition, in the above-mentioned method suitable for producing the present film, a laminate consisting of the present film and a substrate layer may be produced by applying a method of extruding the present dispersion together with the substrate raw material using a co-extruder as an extruder, a method of extruding the present dispersion on a substrate, a method of coating the present dispersion on a long substrate and first forming a coating layer consisting of the present dispersion on the substrate surface, or the like. When the present film is further laminated with a substrate, the peel strength between the film and the substrate is preferably 10 N / cm or more, more preferably 15 N / cm or more, and more preferably 100 N / cm or less.
[0054] The film is useful for antenna parts, printed circuit boards, aircraft parts, automobile parts, sporting goods, food industry products, heat dissipation parts, and the like. Specifically, these include electric wire coating materials (aircraft electric wires, rectangular wires, FFC (Flexible Flat Cable), etc.), enameled wire coating materials used in motors for electric vehicles, etc., power generation coating materials, electrical insulating tapes, insulating tapes for oil drilling, oil transport hoses, hydrogen tanks, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), carrier films for fuel cells, tape base films for the semiconductor manufacturing process (dicing tape, pick-up tape, etc.), release films for semiconductor molding, liquid crystal antennas, reflectors, transmission lines, COF (Chip on Fuel) base films for electrostatic chucks for semiconductor manufacturing processes, electrostatic chucks for display manufacturing processes, copy rolls, furniture, automobile dashboards, covers for home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushes, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, food transport belts, etc.), tension ropes, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts for centrifugal pumps, chemical and water supply pumps, tools (shovels, files, drills, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, racket strings, dies, toilets, container coating materials, heat dissipation boards for mounting power devices, heat dissipation parts for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS They are useful as FETs, CPUs, heat dissipation fins, metal heat sinks, blades for wind turbines, wind power generation equipment, and aircraft, housings for personal computers and displays, electronic device materials, interior and exterior parts of automobiles, sealing materials for processing machines and vacuum ovens that perform heat treatment under low oxygen conditions, plasma processing equipment, heat dissipation parts in processing units for sputtering and various dry etching equipment, and electromagnetic wave shielding. Furthermore, the present film is particularly useful as an electromagnetic wave reflector (reflector array), also known as a metasurface reflector, a metasurface substrate, a solar cell surface release plate, or other solar cell module component, or a transparent cover film in various electronic devices such as smartphones and tablet computers that are equipped with a display panel, such as a liquid crystal, organic electroluminescence, or OLED display panel, and a transparent antenna.
[0055] Although the present film and the manufacturing method of the present film have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the present film may have any other configuration in addition to the configurations of the above-mentioned embodiments, or may be replaced with any configuration that produces a similar effect. Furthermore, the manufacturing method of the present film may have any other process in addition to the configurations of the above-mentioned embodiments, or may be replaced with any process that produces a similar effect. EXAMPLES
[0056] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [F Polymer] F particle 1: containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of TFE units, NAH units, and PPVE units, in that order, and having a carbonyl group-containing group with a carbon atom number of 1×10 constituting the polymer main chain 6 Particles of tetrafluoroethylene polymer (melting point: 300°C) with 1000 particles per particle (D50: 2.0 μm, specific surface area: 7 m 2 / g) F particle 2: Contains 97.5 mol% TFE units and 2.5 mol% PPVE units, in that order, and the number of carbonyl group-containing groups is 1×10 6 Particles (D50: 2.5 μm, specific surface area: 10 m) made of tetrafluoroethylene polymer (melting temperature: 300°C) with less than 50 particles per unit 2 / g) [Surfactants] Surfactant 1: A nonionic silicone surfactant having a polysiloxane chain in the main chain and a polyethylene oxide group in the side chain. [Water-soluble polymer] Water-soluble polymer 1: Hydroxyethyl cellulose
[0057] 2. Dispersion liquid production example [Production Example 1] F particles 1, surfactant 1, water-soluble polymer 1, and water were placed in a pot, and zirconia balls were then placed in. The pot was then rolled at 150 rpm for 1 hour to obtain dispersion liquid 1 containing F particles 1 (35 parts by mass), surfactant 1 (5 parts by mass), water-soluble polymer 1 (0.1 parts by mass), and water (59.9 parts by mass). 1.44 ml of dispersion 1 was taken and diluted 250 times. The entire amount was then passed through a particle size distribution measuring device (AccuSizer (registered trademark) A7000APS manufactured by Japan Entegris Co., Ltd., using an LE400 sensor) to measure the particle concentration with particle diameters of 20 to 80 μm, which was 20 particles / ml.
[0058] [Production Example 2] Dispersion liquid 2 containing F particles 2 (35 parts by mass), surfactant 1 (5 parts by mass), water-soluble polymer 1 (1.0 part by mass) and water (59.0 parts by mass) was obtained in the same manner as in Production Example 1, except that F particles 2 were used instead of F particles 1. 1.44 ml of Dispersion Liquid 2 was taken, and the concentration of particles with particle sizes of 20 to 80 μm was measured in the same manner as in Production Example 1, and was found to be 20 particles / ml.
[0059] 3. Example of long film production and evaluation [Example 1] Dispersion liquid 1 was coated on one side of a support substrate using a roll-to-roll process with a small diameter gravure reverse method to form a coating layer with a length of 1,200 mm in the short direction (TD direction), and the coating layer was passed through a ventilated drying oven at an oven temperature of 70°C for 5 minutes to perform the first heating, and then passed through a ventilated drying oven at an oven temperature of 150°C for 3 minutes to perform the second heating, thereby forming a support substrate having a dry film containing F particles 1 on its surface. Furthermore, this support substrate was passed through a far-infrared furnace at a furnace temperature of 350°C for 5 minutes to melt and sinter the F particles 1, and a support substrate was obtained in which a resin layer (thickness 200μm) containing the melted and sintered product of the F particles 1 was formed on the surface of the copper foil. This support substrate was sandwiched between a first cooling roll at 200°C and a quenching roll, which is a metal elastic roll controlled at 90°C. At this time, a slit-shaped air flow at 200°C was blown uniformly in a line in the width direction of the first cooling roll at a wind speed of 15m / sec from an air knife (height 50mm) installed in a vertical direction to the tangent line contacting the first cooling roll toward the first cooling roll. The F polymer 1 was passed through the first cooling roll and then the second cooling roll at 90°C, and after removing the support substrate, it was taken up by a take-up roll at 90°C to obtain a long film 1 having a width of 1200mm (i.e., the short side direction (TD direction) is 1200mm) and a thickness of 200μm. The obtained long film 1 was divided in the short direction (TD) of the long film 1 at 200 mm intervals, and the endmost divided parts were designated as the TD end parts, and the central divided part was designated as the TD central part, and samples were cut out from each of them. Using a laser microscope (Keyence Corporation's shape analysis laser microscope "VK-X150"), the maximum height Sz at the center of the surface of each sample was measured in accordance with ISO 25178. As a result, the maximum height Sz value at the end in the TD direction (end Sz value) was 2.2 μm, the maximum height Sz value at the center in the TD direction (center Sz value) was 1.8 μm, and the ratio of the end Sz value to the center Sz value was 1.2.
[0060] [Example 2] A long film 2 was obtained in the same manner as in Example 1, except that the temperature of the slit-like air flow was 50°C. For the obtained long film 2, samples were cut out in the same manner as in Example 1, and the maximum height Sz of the surface at the center of each sample was measured in the same manner as in Example 1. As a result, the maximum height Sz value of the end in the TD direction (end Sz value) was 2.1 μm, the maximum height Sz value of the center in the TD direction (center Sz value) was 1.4 μm, and the ratio of the end Sz value to the center Sz value was 1.5. The occurrence of cracks was visually observed on the surface of the long film 2.
[0061] [Example 3] A long film 3 was obtained in the same manner as in Example 1, except that the wind speed of the slit-like air flow was 5 m / s. For the obtained long film 3, samples were cut out in the same manner as in Example 1, and the maximum height Sz of the surface at the center of each sample was measured in the same manner as in Example 1. As a result, the maximum height Sz value of the end portion in the TD direction (end Sz value) was 3.8 μm, the maximum height Sz value of the center portion in the TD direction (center Sz value) was 2.0 μm, and the ratio of the end Sz value to the center Sz value was 1.9.
[0062] [Example 4] A long film 4 was obtained in the same manner as in Example 1, except that Dispersion Liquid 2 was used instead of Dispersion Liquid 1. A sample was cut out from long film 4 in the same manner as in Example 1. The total light transmittance and haze of the film were measured in accordance with JIS R 3106:2019 using a haze meter NDH-5000W manufactured by Nippon Denshoku Industries Co., Ltd. for samples cut out from the center of the TD direction of the long film 1 obtained in Example 1 and the long film 4 obtained in Example 4. The results are shown in Table 1.
[0063] [Table 1] [Industrial Applicability]
[0064] The long film of the present invention has excellent heat resistance and electrical properties based on the tetrafluoroethylene-based polymer, and further has excellent optical properties, and therefore can be effectively used for applications such as reflectors such as metasurface-based reflectors, solar cell modules, transparent antennas, and cover films.
Claims
1. A long film containing a tetrafluoroethylene-based polymer, wherein when the short direction (TD) of the long film is divided at 200 mm intervals, the endmost divided parts are defined as TD end parts and the central divided part is defined as the TD central part, and the maximum height Sz value (end Sz value) of the TD end parts and the maximum height Sz value (central Sz value) of the TD central part are each 0.5 μm or more, as defined in ISO 25178, and the ratio of the end Sz value to the central Sz value is in the range of 1±0.5, and the total light transmittance of the film defined in JIS R 3106 is 90% or more and the haze is less than 1.5%, and the long film has a thickness of 10 μm or more and a width of 1,000 mm or more.
2. The long film according to claim 1, wherein the tetrafluoroethylene-based polymer is a heat-meltable tetrafluoroethylene-based polymer having a melting point of 260 to 320°C.
3. The heat-fusible tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and a carbonyl group-containing group is a unit having a carbon number of 1×10 carbon atoms constituting the polymer main chain. 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol % or more but less than 97.5 mol % and more than 2.5 mol % but not more than 10 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 2. The length film of claim 1, wherein the polymer has less than 100 per unit area.
4. The method for producing a long film according to any one of claims 1 to 3, comprising extruding a dispersion liquid containing 100 parts by mass of tetrafluoroethylene-based polymer particles having an average particle size of 1 μm or more and less than 10 μm and 80 to 300 parts by mass of water, the dispersion liquid having a particle concentration of 5 to 100 particles / ml having a particle size of 20 to 80 μm as measured by a particle counter, forming a film containing the tetrafluoroethylene-based polymer, heating the film to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer, and cooling at 50 to 100 ° C. / min; or applying the dispersion liquid to a substrate to form a coating layer made of the dispersion liquid on the surface of the substrate, heating the substrate having the coating layer to form a resin layer containing a molten sintered body of the tetrafluoroethylene-based polymer on the surface of the substrate, and cooling at 50 to 100 ° C. / min.
5. The method according to claim 4, wherein the tetrafluoroethylene polymer is a heat-fusible tetrafluoroethylene polymer having a melting point of 260 to 320°C.
6. The heat-fusible tetrafluoroethylene-based polymer contains, in this order, more than 97.5 mol % and less than 99.5 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), and a carbonyl group-containing group is a unit having a carbon number of 1×10 carbon atoms constituting the polymer main chain. 6 or a polymer having 100 or more per unit, or a polymer containing 90 mol % or more but less than 97.5 mol % and more than 2.5 mol % but not more than 10 mol % of units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether), respectively, in that order, and the number of carbonyl group-containing groups is 1×10 6 The method of claim 4, wherein the polymer has less than 100 per unit area.
7. The method according to claim 4 , wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more.
8. The method according to claim 4, wherein the dispersion further comprises 5 to 20 parts by mass of a water-soluble solvent having a surface tension of 20 to 30 mN / m.
Citation Information
Patent Citations
Substrate for printed wiring board and method for manufacturing same, printed wiring board and method for manufacturing same, and resin base material
WO2016104420A1